Detection of Cash Flow Shenanigans in The Financial Reports of PT Waskita Karya Tbk - Natalis Christian; Pina Pina; Christian Christian; Versia Silvana (Lafadz Jaya Publisher, 2023)
To better understand if fraud occurs in the financial reports generated by PT Waskita Karya Tbk in 2020–2022, the research problem is linked to the Cash Flow Shenanigans hypothesis. Positive and negative aspects of the contemporary, still-evolving age exist, such as an increase in dishonesty or fraud. Intentional deception has the dual goals of deceiving others and enhancing one's personal benefit. Financial statements that are false, especially those that mention cash flow, are one of the most typical forms of fraud. The information reviewed in this article suggests that PT Waskita Karya Tbk may be using the company's cash flow to conduct fraud or perpetrate it again. Using the company's cash flow ratio and keywords from the available references, this research approach combines qualitative and quantitative analysis. According to reports, the company transferred monies intended for financing activities to operational funds in the first cash flow scam. Reviewing the study's findings revealed that the company had stolen money. The fourth Cash Flow Shenanigan is an increase in operational cash flow caused by unsustainable operations. Finding out if PT Waskita Karya Tbk has ever engaged in fraud is vital since fraud may hurt all parties, especially investors.